Context and Communication - Cappelen, Herman (Contemporary Introductions to Philosophy of Language Ser., 2016)
Context and Communication provides an introduction to a central theme in the study of language: the idea that what we say (or ask, or think) depends on the context of speech and thought. It explores key data, questions, concepts, and theories of context sensitivity, and is written to be accessible to those with no prior knowledge of the subject.